From Self Reliance to Spiritual Delusion: A Metaphorical Interpretation of Hawthorne’s Short Stories - Shaheen, Fouzia; Anwar, Behzad; Rasool, Shamshad (Annals of Human and Social Sciences, 2023)
Emerson's concept "Self-reliance" is an epitome of transcendental philosophy, in which he relates intellectual thought with mystic affluence. Hawthorne, too, in his short stories: "Young Goodman Brown", "The Minister's Black Veil", "The Man of Adamant," and "Ethan Brand," relates the intellectual struggle of his characters to a spiritual experience. These stories reflect the influence of Emerson's doctrine on the one hand, and indicate Hawthorne's anti-transcendental approach on the other hand. The objective of this research is to explore the metaphorical constructions of self-reliance in terms of spiritual delusion. Textual Analysis has been employed to explore the thematic pattern in the stories. Emerson's concept of self-reliance serves as a theoretical framework. The study explores that Hawthorne construes the philosophical inclinations of his age in metaphorical terms and brings home his own views about self-sufficiency and spirituality. The character’s spiritual quest based on independent thinking proves to be fake. Their intuitive comprehension is neither accepted as reality nor adopted as a belief. Their independent thinking turns to be delusion, and they become victims of their immediate cognition. This study also finds that Hawthorne makes his readers careful about their insight without supporting any particular creed. Thus, through the genre of short story, the philosophy of his age has been translated into exotically new terms.